2016
DOI: 10.1007/s11695-016-2438-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Bariatric Surgery: Systematic Review and Meta-Analysis

Abstract: Enhanced recovery after surgery (ERAS) protocol is well established in many surgical disciplines and leads to a decrease in the length of hospital stay and morbidity. Multimodal protocols have also been introduced to bariatric surgery. This review aims to evaluate the current literature on ERAS in obesity surgery and to conduct a meta-analysis of primary and secondary outcomes. MEDLINE, Embase, Scopus and Cochrane Library were searched for eligible studies. Key journals were hand-searched. We analysed data up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
135
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(151 citation statements)
references
References 37 publications
8
135
0
8
Order By: Relevance
“…Numerous studies have demonstrated that application of the ERAS protocol is associated with significant shortening of LOS [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that application of the ERAS protocol is associated with significant shortening of LOS [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies and meta-analyses have shown that patients obtained many benefits such as less pain, earlier intestinal function recovery, shorter hospital stay, less medical expenses, and higher medical satisfaction by implementing the ERAS programs. [9][10][11][12] To provide further evidence for effectiveness of ERAS programs in hepatectomy, a RCT was carried out to compare the perioperative effects between ERAS group and CS group in patients undergoing hepatectomy. The study was approved by the ethics committee of the First Affiliated Hospital of University of South China.…”
mentioning
confidence: 99%
“…These conflicting findings highlight the complexity of the topic and prospective studies are needed to better understand patient and surgeon decision making, develop standardized management plans, and to assess the impact of interventions. Enhanced recovery pathways have demonstrated significant improvements in perioperative care by standardizing care [56] and adoption of standardized protocols may help reduce underlying implicit bias that can result in outcome disparities [57,58].…”
Section: Discussionmentioning
confidence: 99%